2021
DOI: 10.1021/acscatal.1c01587
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Theoretical Study on Siloxy-Based Molybdenum and Tungsten Alkylidyne Catalysts for Alkyne Metathesis

Abstract: A combined spectroscopic and theoretical study on triphenyl-and dimethyl-phenyl siloxy molybdenum and tungsten alkylidyne catalysts for alkyne metathesis is reported. Using NMR, X-ray, UV−vis, and resonance Raman spectroscopy and density functional theory calculations, the influence of different ligand systems and metal centers on the geometric and electronic structure and thermochemistry of different intermediates is investigated, that is, the starting alkylidyne and the derived metallacyclobutadiene (MCBD) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 66 publications
0
43
0
Order By: Relevance
“…We found that the 95 Mo δ iso are slightly but significantly different in the solid state compared to in solution, particularly for the silanolate complexes, indicating the substantial influences of dynamic and/or conformational effects (vide infra). 34 The solid-state 95 Mo δ iso are correlated (SI Section S3, Figures S43-S44) with the 13 C δ iso values, but one can readily distinguish the (fluoro)alkoxide series from the silanolate series as the latter exhibit 95 Mo chemical shifts significantly more deshielded than expected based on their 13 C chemical shifts. The 95 Mo quadrupolar coupling constants (C Q ) were also estimated to be between 2.0 and 4.5 MHz, typically significantly lower that the values calculated from first principles (SI Table S4.1), likely due to dynamic effects, present even under the low temperature measurement conditions.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…We found that the 95 Mo δ iso are slightly but significantly different in the solid state compared to in solution, particularly for the silanolate complexes, indicating the substantial influences of dynamic and/or conformational effects (vide infra). 34 The solid-state 95 Mo δ iso are correlated (SI Section S3, Figures S43-S44) with the 13 C δ iso values, but one can readily distinguish the (fluoro)alkoxide series from the silanolate series as the latter exhibit 95 Mo chemical shifts significantly more deshielded than expected based on their 13 C chemical shifts. The 95 Mo quadrupolar coupling constants (C Q ) were also estimated to be between 2.0 and 4.5 MHz, typically significantly lower that the values calculated from first principles (SI Table S4.1), likely due to dynamic effects, present even under the low temperature measurement conditions.…”
mentioning
confidence: 98%
“…n SiO] 3 MoC(Ar) (n=0-3), the 95 Mo δ ⊥ increases linearly with the number of phenyl substituents from 785 to 950 ppm indicating the significant influence of the ligand π system, which could be modulated by intramolecular dispersion interactions that were recently evidenced by UV-visible spectroscopy. 13 Both these examples highlight the utility of 95 Mo chemical shifts as a highly resolved probe of electron delocalization through the ligand π system due to their direct dependence on the energy of the Mo≡C π bond and the Mo d orbitals.…”
mentioning
confidence: 98%
See 3 more Smart Citations